2020
DOI: 10.3390/genes12010035
|View full text |Cite
|
Sign up to set email alerts
|

RET Copy Number Alteration in Medullary Thyroid Cancer Is a Rare Event Correlated with RET Somatic Mutations and High Allelic Frequency

Abstract: Copy number variations (CNV) of the RET gene have been described in 30% of Medullary Thyroid Cancer (MTC), but no information is available about their role in this tumor. This study was designed to clarify RET gene CNV prevalence and their potential role in MTC development. RET gene CNV were analyzed in 158 sporadic MTC cases using the ION Reporter Software (i.e., in silico analysis) while the multiplex ligation-dependent probe amplification assay (i.e., in vitro analysis) technique was performed in 78 MTC cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…A recent study revealed that RET indels are not uncommon, occurring in up to 17.4% of MTCs, and that these correlate with aggressive disease [58]. RET copy number alterations (CNAs) are found in 13 to 30% of hereditary and sporadic MTCs [66,67]. The presence of RET mutation at both the germline or somatic level was more frequent in tumours with RET CNAs compared to those without (83.3% vs. 42.5%, p = 0.003) [68].…”
mentioning
confidence: 99%
“…A recent study revealed that RET indels are not uncommon, occurring in up to 17.4% of MTCs, and that these correlate with aggressive disease [58]. RET copy number alterations (CNAs) are found in 13 to 30% of hereditary and sporadic MTCs [66,67]. The presence of RET mutation at both the germline or somatic level was more frequent in tumours with RET CNAs compared to those without (83.3% vs. 42.5%, p = 0.003) [68].…”
mentioning
confidence: 99%